Assessment of the Knowledge of the Association between Periodontal Status and Pregnancy Outcome among Obstetricians and Gynecologists - Pradhan, Shaili; Baral, Gehanath; Shrestha, Rejina (Journal of Nepal Health Research Council, 2022)
Background: It has been more than two decades since a link was found between maternal oral health and adverse pregnancy outcome. Obstetricians and gynecologists play a core role in the screening, prevention and referral of the pregnant women for periodontal diseases. Thus, a study was conducted to assess the knowledge of the association between periodontal status and pregnancy outcomes.Methods: An online survey was done by distributing self-administered questionnaire to the obstetricians and gynecologists. The survey consisted of three parts: demographic variables, consent and questionnaire. The qualitative data was recorded and analyzed.Results: Out of 237 participants, 95.8% of the participants agreed that there is a relation between periodontal disease and pregnancy; 73.8% with preterm birth, 60.3% with low birth weight infants and 38.4% with pre-eclampsia.Conclusions: The knowledge of the association between periodontal status and pregnancy outcomes was found to be insufficient. The gynecologists must be provided with periodic orientation to enhance and update their knowledge on maternal periodontal health.Keywords: Adverse pregnancy outcomes; gynecologists; periodontal diseases; pregnancy.